Understanding Forgiveness among Minangnese Ethnicity: The Effect of Religiosity, Agreeableness, and Neuroticism - Nashori, Fuad; Wijaya, Hariz Enggar; Diana, Raden Rachmy (Universitas Islam Indonesia, 2023)
The Minangnese are an ethnic group in Indonesia that reside in West Sumatra. It has characterized by an emphasis on harmony in all aspects of life. Despite this emphasis, the Minangnese recognize that conflict is a natural occurrence. The study aimed to investigate the effect of religiosity and interpersonal attachment on forgiveness through agreeableness and neuroticism in the Minangnese ethnicity. Minangnese ethnic participants were selected by considering the following criteria, namely citizens of and living in West Sumatra Province, claimed to be Minangnese people, Muslim, and living in West Sumatra Province for the last 10 years. Using a stratified cluster random sampling method, 205 Minangnese individuals were recruited and administered five questionnaires to assess forgiveness, agreeableness, neuroticism, religiosity, and interpersonal attachment. The results indicated that religiosity had a significant influence on forgiveness in the Minangnese ethnicity, with this influence being mediated by agreeableness and neuroticism. Specifically, religiosity was found to have a positive effect on emotional stability and a negative effect on neuroticism, as well as reducing hostility and anger and decreasing anxiety. These findings suggest that religiosity and agreeableness may be important factors to consider when seeking to understand and promote forgiveness in the Minangnese ethnicity